Exploring the Link Between the L2 Motivational Self-System and Extensive Reading: Why Do Learners Continue to Engage? - Cahya Intan Syafinaz; Anik Nunuk Wulyani; Sari Karmina (AL-ISHLAH: Jurnal Pendidikan, 2024)
Sustained motivation in extensive reading (ER) is essential for fostering long-term reading habits. The L2 Motivational Self-System (L2MSS)—comprising the ideal L2 self, ought-to L2 self, and L2 learning experience—provides a framework for understanding motivation in second-language learning contexts. However, the specific role of L2MSS in motivating learners to persist in ER remains underexplored. This explanatory sequential mixed-method study investigated the relationship between L2MSS components and students’ willingness to continue ER. Data were collected from 64 English department students at a university in Malang, Indonesia, through quantitative surveys followed by qualitative interviews to contextualize the findings. The quantitative analysis revealed that the ideal L2 self was the strongest predictor of students’ willingness to engage in ER. The ought-to L2 self and L2 learning experience were found to have a lesser but still notable impact. Qualitative findings indicated that students recognized the value of ER and identified supportive environments, such as positive teacher and peer interactions, as key facilitators of their engagement. The results underscore the primacy of the ideal L2 self in sustaining motivation for ER, while the acknowledgment of ER's benefits and a conducive learning environment also played supportive roles. These findings suggest that educators should emphasize the intrinsic value of ER and cultivate an encouraging environment to strengthen students' self-commitment. The study highlights the importance of fostering the ideal L2 self and promoting supportive ER environments. Educators should actively advocate the value of ER to students and their families to enhance long-term engagement.